Changes in the nanoparticle uptake and distribution caused by an intramacrophagic parasitic infection. Issue 41 (15th October 2021) - Calvo, Alba; Moreno, Esther; Clemente, Unai; Pérez, Enma; Larrea, Esther; Sanmartín, Carmen; Irache, Juan Manuel; Espuelas, Socorro
Abstract : Immunopathological alterations produced by a viscerotropic and intramacrophagic parasite affected NP organ uptake and cellular distribution. Abstract : This study investigates if visceral leishmaniasis (VL) infection has some effects on the organ and cellular uptake and distribution of 100–200 nm near-infrared fluorescently labelled non-biodegradable polystyrene latex beads (PS NPs) or biodegradable polylactic- co -glycolic nanoparticles (PLGA NPs), as this parasitic infection produces morphological alterations in liver, spleen and bone marrow, organs highly involved in NP sequestration. The results showed that the magnitude of the effect was specific for each organ and type of NP. With the exception of the liver, the general trend was a decrease in NP organ and cellular uptake, mostly due to immune cell mobilization and/or weight organ gain, as vascular permeability was increased. Moreover, NPs redistributed among different phagocytic cells to adapt infection associated changes and cellular alterations. In the liver, it is noteworthy that only isolated Kuffer cells (KCs) captured NPs, whereas they were not taken up by KC forming granulomas. In the spleen, NPs redistributed from macrophages and dendritic cells towards B cells and inflammatory monocytes although they maintained their preferential accumulation in the marginal zone and red pulp. Comparatively, the infection rarely affected the NP cellular distribution in the bone marrow. NP cellular target changes in VL infection could affect their therapeutic efficacy and should be considered for more efficient drug delivery.